The Effect of Proposed Exercises On Some Kinematical Variables Of Rotational Back Kick In Taekwondo Fighters Aged 15 – 17 Years Old - Rasheed, Intisar; Abedalelillah, Ahmed (Journal of Physical Education, 2017)
The problem of the research lies in rotational back kicks being used in taekwondo for knock out yet Iraqi fighters have a great weakness in this kick. The aim of the research is to identify some kinmatical variables of rotation back kick in taekwondo as well as designing exercises and finding their effect on back kick. The researcher hypothesized significant statistical differences between pre and posttests in favor of posttests. The researcher used the experimental method to conclude significant statistical differences between pre and posttests in favor of posttests that proves the effect of the proposed exercises. The researcher recommended using modern technologies to detect weaknesses that hinder the player’s development like using small quadricopter in filming the skill as well as using cameras for live performance along with using exercises that suits the skills the fighters use during competition